Associations between language learners` spiritual intelligence, foreign language attitude and achievement motivation: A structural equation approach - Mahmoodi-Shahrebabaki, Masoud (Journal of Interdisciplinary Studies in Education, 2015)
The present study examines the relationships between language learners` Spiritual Intelligence, Achievement Motivation and Foreign Language Attitude. The sample consists of 223 Iranian advanced English language learners. The data were collected by use of Spiritual Intelligence Self-report Inventory, Foreign Language Attitude Scale and Achievement Motivation Questionnaire. Two hypothetical models were proposed for mediation analysis by means of structural equation modeling. The results revealed that foreign language attitude mediates the causal correlations between Spiritual Intelligence and Achievement Motivation. For the second model, however, the intervening effect of Achievement Motivation on the causal paths from Spiritual Intelligence to Foreign Language Attitude was not supported based on the analysis of effects. The results provide new insights and can pave the way for further investigation of the associations between Spiritual Intelligence and other individual differences of language learners.